Manuskrip nusantara di Saint Petersburg: tambahan data - Ogloblin, Alexander K; Revounenkova, Elena V (Universiti Kebangsaan Malaysia, 2007)
Malay, Javanese, Balinese and Batak manuscripts stored in the libraries and museums of St. Petersburg may be few, but some of them have attracted the attention of Russian and other scholars. A copy of the Malay Annals Sulalat as-Salatin (Sejarah Melayu) made in Malacca in 1798 and translated into Russian and studied by Revounenkova, reveals only minor differences in word usage, the use of particles etc. from that which was edited by Munsyi Abdullah. This manuscript is soon to be published with a Russian translation. The three MSS described in this paper requires further analysis. One of them, a Malay manuscript in Javanese pegon script, which has been stored at the Russian National Library since early 19th century, resembles a Javanese primbon Another, a Javanese text of wayang performance, Lampahan Pregiwa, was made for the Russian friends or colleagues of the author, presumably in the 19th or early 20th century in Java. The third, a Javanese mystical Islamic poem (suluk) from the early 17th century contains many peculiarities in script, spelling, and vocabulary. A survey of other St. Petersburg manuscripts from Nusantara and related studies is presented in this paper